Ratio of the Effective Clharge of He Beams Traversing Gaseous and Metallic Cadmium. - Meckbach, W.; Allison, S. K. (American Chemical Society, 1963)
Fil: Meckbach, W. Comisión Nacional de Energía Atómica; Argentina